2020
DOI: 10.1177/1545968319899914
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolism but Not Gray Matter Volume Underlies the Presence of Language Function in the Minimally Conscious State (MCS): MCS+ Versus MCS− Neuroimaging Differences

Abstract: Background. The minimally conscious state (MCS) is subcategorized into MCS− and MCS+, depending on the absence or presence, respectively, of high-level behavioral responses such as command-following. Objective. We aim to investigate the functional and structural neuroanatomy underlying the presence of these responses in MCS− and MCS+ patients. Methods. In this cross-sectional retrospective study, chronic MCS patients were diagnosed using repeated Coma Recovery Scale–Revised assessments. Fluorodeoxyglucose-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 62 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…This is not surprising, as, by definition, on the contrary to MCS+, patients in a MCS− are unable to show that they understand language (e.g., behavioral response to command). In the literature, the clinical subcategorization of MCS is further supported by metabolic differences in areas that are associated with consciousness (i.e., lower metabolism in precuneus and thalamus in MCS−) [41] and with both receptive and expressive language (i.e., lower metabolism in the left middle temporal cortex and lower connectivity between left angular gyrus and left prefrontal cortex in MCS−) [42,43]. The detection of covert cognition in MCS− suggests that, in a fraction of these patients, receptive language impairment might not be the limiting factor when assessing consciousness at the bedside but expressive language impairments (and hence motor limitations) might be.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as, by definition, on the contrary to MCS+, patients in a MCS− are unable to show that they understand language (e.g., behavioral response to command). In the literature, the clinical subcategorization of MCS is further supported by metabolic differences in areas that are associated with consciousness (i.e., lower metabolism in precuneus and thalamus in MCS−) [41] and with both receptive and expressive language (i.e., lower metabolism in the left middle temporal cortex and lower connectivity between left angular gyrus and left prefrontal cortex in MCS−) [42,43]. The detection of covert cognition in MCS− suggests that, in a fraction of these patients, receptive language impairment might not be the limiting factor when assessing consciousness at the bedside but expressive language impairments (and hence motor limitations) might be.…”
Section: Discussionmentioning
confidence: 99%
“…Using fluorodeoxyglucose (FDG)-PET, higher brain glucose metabolism was observed in left-side language-related cortical areas in MCS+ patients compared to MCS − patients. 63 64 65 Stronger brain connectivity in a left frontoparietal network was also observed using both resting state fMRI and FDG-PET in MCS+ compared to MCS − . 63 64 66 A recent study also supports the association between the level of preservation of the language network and the CRS-R auditory subscale scores (including the command-following item).…”
Section: Language Abilities In the Different Doc Entitiesmentioning
confidence: 78%
“…63 64 65 Stronger brain connectivity in a left frontoparietal network was also observed using both resting state fMRI and FDG-PET in MCS+ compared to MCS − . 63 64 66 A recent study also supports the association between the level of preservation of the language network and the CRS-R auditory subscale scores (including the command-following item). 67 By examining white matter integrity, Zheng et al 68 showed an increased structural connectivity for thalamo-premotor and thalamo-temporal pathways in MCS+ compared to MCS− patients.…”
Section: Language Abilities In the Different Doc Entitiesmentioning
confidence: 78%
See 1 more Smart Citation
“…PDOC can be divided into unresponsive wakefulness syndrome (UWS) and minimally conscious state (MCS) according to the degree of retention of awareness ( 6 ). UWS is also traditionally called as vegetative state (VS), and MCS can be further divided into MCS- and MCS+ ( 7 , 8 ). We can use the Coma Recovery Scale Revised (CRS-R) to infer the degree of consciousness retention through the behavioral characteristics of patients and make differential diagnosis for PDOC ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%